Evaluasi Dan Redesain Antarmuka Website megapolitanpos.com Menggunakan Metode Usability Testing Dan Heuristic Evaluation - Tanuwijaya, Jonathan; Prasetyo, Arfhan (Computer Science (CO-SCIENCE), 2025)
Megapolitanpos.com, a Press Council-verified online news portal, faces usability problems such as complex navigation, unorganized layout, and less attractive visual design. This research aims to identify problems, redesign the interface, and improve user satisfaction through Usability Testing and Heuristic Evaluation. From 373 respondents, major problems such as unintuitive navigation, inconsistent news categories, unstructured information, absence of page loading indicators, and lack of user guidance were found. Most of the issues had a severity rating of 2, requiring redesign. The average severity rating obtained was 2.0. Recommendations include improving the category layout, adding loading indicators, tooltips, and arranging information elements logically, while maintaining the blue color as the visual identity. HTML and Bootstrap-based design prototypes designed based on valid and reliable analysis are expected to improve user experience and present information more intuitively.